The Impact of Social, Cultural, and Identity-Related Factors on Delayed Childbearing: A Multi-Center Study - Lei Y; Wang X; Zhou Y; Li Y; Wang L; Jia X; Ma Q; Lin C; Liao J; Li X; Liu T (Risk Management and Healthcare Policy)
Ying Lei,1,* Xiao Wang,2,* Yaling Zhou,3,* Yalan Li,4 Luyao Wang,5 Xiaoying Jia,5 Qingzhan Ma,5 Changsheng Lin,5 Jie Liao,1 Xin Li,5,* Tianjiao Liu6 1Chengdu Wenjiang Maternal and Child Health Hospital, Chengdu, 611130, People’s Republic of China; 2Chengdu Xinjin District Maternal and Child Health Care Hospital, Chengdu, 611430, People’s Republic of China; 3Chengdu Gaoxin Southwest Children’s hospital, Chengdu, 610047, People’s Republic of China; 4The Fourth People’s Hospital of Chengdu, School of Medicine, University of Electronic Science and Technology of China, Chengdu, 611731, People’s Republic of China; 5Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, West China Second Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China; 6Chengdu Women’s and Children’s Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, 611731, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie Liao, Wenjiang Maternal and Child Health Hospital, Chengdu, Sichuan, 611130, People’s Republic of China, Email 56305039@qq.com Tianjiao Liu, Chengdu Women’s and Children’s Central Hospital, 1617 Riyue Avenue, Qingyang District, Chengdu, 611731, People’s Republic of China, Email liutianjiaotj66@126.comBackground: Delayed childbearing has become an increasingly prevalent trend, influenced by various psychological and social factors. This study aimed to explore the impact of these factors on the timing of childbirth among women of reproductive age.Methods: A cross-sectional study was conducted with 1,128 women attending their first prenatal visit at six hospitals between January and December 2023. Sociodemographic, psychological, and health-related data were collected through structured interviews and self-administered questionnaires. Bivariate and multivariate analyses were performed to identify significant predictors of delayed childbearing.Results: Reproductive health issues, educational level, employment status, career advancement aspirations, and age-related anxiety were significantly associated with delayed childbearing. Multivariate logistic regression revealed that reproductive health issues (OR = 2.70), educational level (OR = 1.84), and career aspirations (OR = 2.53) were independent predictors of delayed childbearing. Interestingly, age-related anxiety was associated with an increased likelihood of earlier reproductive decision-making, reducing the odds of delayed childbirth by 69% (OR = 0.31, 95% CI: 0.23– 0.56, p < 0.001). Subgroup analysis indicated that both low-income and high-income women were more likely to delay childbirth compared to women with medium income (p < 0.05).Conclusion: Psychological and social factors, including career goals, educational attainment, and reproductive health issues, play a critical role in the decision to delay childbearing. Understanding these influences is essential for developing policies and interventions that support women in making informed reproductive choices. Further research with more diverse populations is needed to confirm these findings and explore the broader societal implications.Keywords: delayed childbearing, educational level, fertility decisions, reproductive age